A novel gedunin-2-hydroxypropyl-β-cyclodextrin inclusion complex improves anti-nociceptive and anti-inflammatory activities of gedunin in rodents (Nigerian Journal of Physiological Sciences, 2022)
Gedunin is a bioactive compound, obtained from Entandrophragma angolense (EA), which has limited therapeutic usefulness due to poor aqueous solubility and first-pass effects. Cyclodextrins are cyclic oligosaccharides that form complexes with poorly soluble compounds, thus enhancing their pharmacological activity. In this article, we evaluated the pharmacological activities of gedunin-2-hydroxypropyl-β-cyclodextrin complex (GCD) in rodents. The antinociceptive activity of GCD (50, 100, 200 mg/kg) and Gedunin (50mg/kg) was tested in acetic acid-induced writhing and formalin-induced paw licking in mice. The anti-inflammatory activity was investigated in carrageenan-induced paw oedema and air pouch inflammation models in rats. Leucocytes counts, Tumour Necrosis Factor-alpha (TNF-α) level, nitric oxide, malondialdehyde, reduced glutathione, and myeloperoxidase enzyme activities were assessed in the air pouch exudate. The GCD (200mg/kg) significantly decreased writhing response, reduced licking duration and decreased oedema compared with gedunin and control. Exudate volume and leucocyte count were significantly reduced by GCD (200 mg/kg), it decreased myeloperoxidase activity and inhibited TNF-α release. The carrageenan-induced GSH depletion, increased malondialdehyde and nitrite levels were significantly reversed by GCD (200 mg/kg) relative to gedunin and control.  The GCD complex demonstrated significant antinociceptive and anti-inflammatory activities relative to gedunin alone via mechanisms associated with inhibition of oxidative stress and inflammation in rodents